Practical training report Sarawak Foundation / Monalissa Mariah Brain - Brain, Monalissa Mariah (University Technology MARA Sarawak, 2017)
Yayasan Sarawak was an organisation grant scholarship to provide financial assistance in any form especially to the students from Sarawak and generally to the Peninsular Malaysia students in order to pursue their studies in schools, colleges, universities or institutions of higher leamin within Malaysia or abroad on such terms and conditions as the Board deems fit or proper. Yayasan Sarawak actively to promote improvement and opportunities for education for the citizen of Sarawak in particular and Malaysia in general for both locally and in any higher learning education around the world but focus to the Universities in Malaysia. Besides that, the organisation also grant and arrange for the award by other bodies of scholarships or other educational assistance for the people of Sarawak or any Malaysian citizen whenever it deems fit to do so.